2008
DOI: 10.1089/jmf.2007.0500
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Mineral Contents of Capers (Capparis spp.) Seed Oils Growing Wild in Turkey

Abstract: Minor and major mineral contents of seed oils of Capparis ovata Desf. var. canescens (Coss.) Heywood and Capparis spinosa var. spinosa used as pickling products in Turkey were determined by inductively coupled plasma atomic emission spectrometry. The seed oils contained Al, P, Na, Mg, Fe, and Ca, in addition to fatty acids. The highest mineral concentrations measured were 14.91-118.81 mg/kg Al, 1,489.34-11,523.74 mg/kg P, 505.78-4,489.51 mg/kg Na, 102.15-1,655.33 mg/kg Mg, 78.83-298.14 mg/kg Fe, and 1.04-76.39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…According to the degree of fermentation of tea, we can divide tea into three major categories: unfermented tea, semifermented tea, and full-fermented tea (31), and the representative tea varieties are green tea, oolong tea, and black tea. Studies have shown that green tea, oolong tea, black tea, and their main active ingredients all have certain lipid-lowering and weight loss effects (43)(44)(45)(46)(47), and their main active ingredients are catechins, caffeine, tea pigments, and so on (48), which mainly play a role by increasing energy consumption, changing lipid metabolism, and regulating appetite. Catechins are one of the main components of tea polyphenols, among which EGCG is the highest.…”
Section: Discussionmentioning
confidence: 99%
“…According to the degree of fermentation of tea, we can divide tea into three major categories: unfermented tea, semifermented tea, and full-fermented tea (31), and the representative tea varieties are green tea, oolong tea, and black tea. Studies have shown that green tea, oolong tea, black tea, and their main active ingredients all have certain lipid-lowering and weight loss effects (43)(44)(45)(46)(47), and their main active ingredients are catechins, caffeine, tea pigments, and so on (48), which mainly play a role by increasing energy consumption, changing lipid metabolism, and regulating appetite. Catechins are one of the main components of tea polyphenols, among which EGCG is the highest.…”
Section: Discussionmentioning
confidence: 99%
“…(16) Furthermore many bioactive compounds such as saccharides, glycosides, alkaloids, terpenoids, volatile oils, fatty acids, steroids and several minerals present in caper may directly or indirectly influence glucose or insulin metabolism. (17) Considering the present study and previous data, caper can be used as an adjuvant agent for treatment of diabetic patients but this requires more additional validation studies. However it should be also noted that small sample size and lack of identification of the active constituent(s) responsible for the effects of caper fruit extract are limitations of the present study.…”
Section: Discussionmentioning
confidence: 67%
“…In buds and flowers, there were both alpha-(49.12±17.48 and 28.68±9.13 mg/100 g FW, respectively) and gamma-tocopherol (48.13±15.08 and 27.8±16.01 mg/100 g FW, respectively. The combined content of pro-vitamin A and vitamin E in capers encourages researchers to explore new active principles of great pharmaceutical importance from this plant [91] [ Table 1 ].…”
Section: Anti-parasitic Effectsmentioning
confidence: 99%
“…[83] Plant is a richest source of beta-carotene (14%), oils and fats [90] and minerals. [91] Fruits are used to make pickles that also possess very high nutritive value. Its flower buds contain ample amount of vitamins, which showed high anti-oxidant activity while stem, leaves and flowers contain phenolic compounds, which showed antioxidant, anticancer, antimicrobial, anti-protozoal, antiviral and immunomodulatory activity [92][93][94] Its seed proteins contain anticancer activity and inhibit proliferation of hepatoma HepG2 cells, colon cancer HT29 and breast cancer MCF-7 cells.…”
Section: Anti-parasitic Effectsmentioning
confidence: 99%